The digital divide has grown old: Determinants of a digital divide among seniors - Friemel, Thomas N (New media & society, 2016)
The diffusion of the Internet is reaching a level between 80% and 90% in Western societies. Yet, while the digital divide is closing for young cohorts, it is still an issue when comparing various generations. This study focuses specifically on the so-called ‘grey divide’, a divide among seniors of age 65+ years. Based on a representative survey in Switzerland (N = 1105), it is found that Internet use is strongly skewed in this age group leading to a partial exclusion of the old seniors (70+). Logistic regression shows that gender differences in usage disappear if controlled for education, income, technical interest, pre-retirement computer use and marital status. Furthermore, the social context appears to have a manifold influence on Internet use. Encouragement by family and friends is a strong predictor for Internet use, and private learning settings are preferred over professional courses. Implications for digital inequality initiatives and further research are discussed.